Sacred words orality, literacy, and religion - Blok, Josine.; Lardinois, A. P. M. H.; Poel, Marc van der. (Mnemosyne, Supplements, 2011)
A prevalent view in the current scholarship on ancient religions holds that state religion was primarily performed and transmitted in oral forms, whereas writing came to be associated with secret, private and marginal cults, especially in the Greek world. In Roman times, religions would have become more and more bookish, starting with the Sibylline books and the Annales Maximi of the Roman priests and culminating in the canonical gospels of the Christians. It is the aim of this volume to modify this view or, at least, to challenge it. Surveying the variety of ways in which different types of texts and oral discourse were involved in ancient Greek and Roman religions, the contributions to this volume show that oral and written forms were in use for both Greek and Roman state and private religions.